Distinct functions for thyroid hormone receptors alpha and beta in brain development indicated by differential expression of receptor genes. - Forrest, D (1991)
Thyroid hormones are essential for correct brain development, and since vertebrates express two thyroid hormone receptor genes (TR alpha and beta), we investigated TR gene expression during chick brain ontogenesis. In situ hybridization analyses showed that TR alpha mRNA was widely expressed from early embryonic stages, whereas TR beta was sharply induced after embryonic day 19 (E19), coinciding with the known hormone-sensitive period. Differential expression of TR mRNAs was striking in the cerebellum: TR beta mRNA was induced in white matter and granule cells after the migratory phase, suggesting a main TR beta function in late, hormone-dependent glial and neuronal maturation. In contrast, TR alpha mRNA was expressed in the earlier proliferating and migrating granule cells, and in the more mature granular and Purkinje cell layers after hatching, indicating a role for TR alpha in both immature and mature neural cells. Surprisingly, both TR genes were expressed in early cerebellar outgrowth at E9, before known hormone requirements, with TR beta mRNA restricted to the ventricular epithelium of the metencephalon and TR alpha expressed in migrating cells and the early granular layer. The results implicate TRs with distinct functions in the early embryonic brain as well as in the late phase of hormone requirement.